Evolução da cadeia produtiva de avicultura de corte - Rocha, Natymyriara Fernandes (Universidade Federal do Tocantins, 2021)
Poultry farming started at the end of the 19th century, on the Asian continent. Before that, birds were used as fighting animals, and also for ornamentation. From the 19th century onwards, they began to consume eggs and poultry meat. In Brazil, poultry farming began in the 1930s, when small producers began to raise free-range chickens. In the 70's, began to modernize and improve poultry farming, intensifying production. The facilities where the animals are raised are largely responsible for good results in poultry farming. Because the better the conditions of the environment in which the birds live, the better they express their productive characteristics, resulting in better and faster production. Then comes the need to study and analyze the improvement of technologies, without leaving aside the economic issue, which is also extremely important for good production. Brazil finds itself today as the largest exporter of chicken meat in the world. Thus, the finishing of the animals, with the shortest time, is of paramount importance to remain on this podium. And for this to happen, innovations in ambience, which is the title of this review, are extremely necessary to obtain better results.